Evaluating Direct Pointing and Indirect Cursor Interactions with Fitts' Law in Stereoscopic Environments - Dino Caesaron; Chiuhsiang Joe Lin; Ilma Mufidah; Anastasia Febiyani (Journal of Engineering and Technological Sciences, 2022)
The development of virtual environment research has reached the stage of human interaction with three-dimensional (3D) objects. In this study, Fitts' method was used to such interaction techniques in virtual environment, and the Fitts' law applicability in 3D virtual environment was also considered. The experiment included two modes of interaction: direct interaction and indirect interaction that utilize different techniques depending on how users interact with 3D objects. Both interaction techniques were conducted in three indexes of difficulties and three egocentric target distances (a distance from participant to target). Movement time and throughput were measured for each interaction technique. The results show that the direct pointing technique is more efficient for interaction with the targets close to the participant, while the indirect cursor technique may be a viable option for targets further away from participant. Throughputs were found to be significantly higher for the direct pointing technique compared to the indirect cursor technique. The results of the mean movement time were highly correlated with the targets' index of difficulty for all interaction techniques, supporting evidence that Fitts' law can be applied to the interactions in 3D virtual environment. Based on the results, developers of VE application may relate to these findings in designing proper users' interactions.